HIERARCHICAL 3D MODELING IN COMPLEX CARBONATE RESERVOIR by COMBINING DETERMINISTIC AND STOCHASTIC APPROACH - Natasia, Nanda; Alfadli, Muhammad Kurniawan (Bulletin of Scientific Contribution, 2019)
ABSTRACTThis paper shows how to model the 3d complex carbonate reservoir by combining deterministic and stochastic method. 3d facies model is the most important step in building reservoir static model because the distribution of another properties will depends on this model. a good facies model is needed in building a good model. The nature complexity of carbonate facies  itself makes the modeling are even more chalangging. Deterministic geological interpretation is  modelled by trend modeling while the rock type distribution is distributed inside each facies stochastically. This field is divided into five zones. These zones represent depositional cycle occurred within carbonate formation. The facies is divided into four facies; Reef, Lagoon, Platform, and slope. a reservoir rock type was done by using RT distributions.  According to Geological concept, reservoir quality distributions have different trend either vertical or horizontal. Horizontally, a good reservoir should be located in Reef facies and the poor reservoir quality should be located in slope facies. Vertically, reservoir quality should get better from bottom to top in every reservoir zoneKeywords: Pore types, Diagenetic prosses, Carbonate Reservoir